THE SOCIAL REPRESENTATION OF DRUGS FROM A GROUP OF INMATES AT TWO MEXICAN PRISONS - Castellanos López, Gloria Estela (Anales de Psicología / Annals of Psychology, 2007)
The purpose of this work is to provide a discursive approach to social representation from a group of inmates regarding drugs. We worked with 135 inmates from two Mexican jails, whom were individually interviewed with the objective of obtaining a discourse regardless their drugs’ experience. Results obtained shows 3 main categories: problems, negative emotions and motives, where experiences which give a sense to social representation are lied to forbearing losses, being incarcerated, incapacity for facing their consumption and death as possibility. By one hand, feeling anxiety, despair, fear, aggressiveness; by other hand, pleasure, avoid reality and sense of belongness. The searching a hole look which includes aspects such as socials representations and their impact in the sense of giving consumption, to understand how each person structures significations which holds their acts in specified context, allowing to draw an effective intervention programs which easy the modification of their social representations through a healthier life.